2009
DOI: 10.1177/1368430209344868
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of Ambiguous Human/Ape Faces: Protection of Ingroup but Not Outgroup Humanity

Abstract: In two studies, we tested the hypothesis that categorization of ambiguous human/ape faces depends on group membership: people are inclined to protect ingroup humanity, but not that of the outgroup. We used as stimuli: human, ape, ambiguous human/ape faces. Ambiguous human/ape faces were generated using a computerized morphing procedure. Participants categorized stimuli as human or ape. Two conditions were introduced: in the ingroup condition, participants were informed that human exemplars were ingroup members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 37 publications
(48 reference statements)
2
34
0
16
Order By: Relevance
“…Groups are likened to animals when they are perceived as lacking the unique features of human species; groups are likened to machines or robots when they are perceived as lacking the basic traits of human nature, that can be shared with animals (e.g., warmth, emotional responsiveness). Research has demonstrated that people use both types of dehumanization (for animalistic dehumanization, see Capozza, Boccato, Andrighetto, & Falvo, 2009;Goff, Eberhardt, Williams, & Jackson, 2008;Viki et al, 2006; for mechanistic dehumanization, see Andrighetto, Baldissarri, Lattanzio, Loughnan, & Volpato, 2014;Loughnan, Haslam, & Kashima, 2009).…”
Section: Humanity Attributionsmentioning
confidence: 99%
“…Groups are likened to animals when they are perceived as lacking the unique features of human species; groups are likened to machines or robots when they are perceived as lacking the basic traits of human nature, that can be shared with animals (e.g., warmth, emotional responsiveness). Research has demonstrated that people use both types of dehumanization (for animalistic dehumanization, see Capozza, Boccato, Andrighetto, & Falvo, 2009;Goff, Eberhardt, Williams, & Jackson, 2008;Viki et al, 2006; for mechanistic dehumanization, see Andrighetto, Baldissarri, Lattanzio, Loughnan, & Volpato, 2014;Loughnan, Haslam, & Kashima, 2009).…”
Section: Humanity Attributionsmentioning
confidence: 99%
“…Despite research has investigated a wide range of intergroup relations, such as ethnic (e.g., Gaunt, ), regional (e.g., Capozza, Andrighetto, Di Bernardo, & Falvo, ; Capozza, Boccato, Andrighetto, & Falvo, ), and minimal groups (e.g., Demoulin et al., ), the concept of dehumanization has not received systematic attention by researchers analyzing the relationship between health care professionals and patients. Indeed, many aspects of modern medicine are associated with a dehumanized representation of patients (Haslam, ); for instance, illness‐related labels (e.g., schizophrenic, psychotic, heart patient) are used to refer to patients, patients' individuality is denied, and great importance is placed on technology.…”
Section: Humanness Attributionsmentioning
confidence: 99%
“…Moreover, the SCCB predicts that all of these processes are similarly embodied via a vertical metaphor that associates the ultimate good, righteousness, and the sacred as "high" and the ultimate evil and pollution as "low." Recent treatments of the psychological processes of dehumanization and anthropomorphism have focused on the attribution of personality traits and emotions that are more or less uniquely associated with humanity (e.g., Haslam, 2006;Leyens et al, 2001;; for some exceptions, see, e.g., Boccato et al, 2008;Capozza et al, 2009;Goff et al, 2008). The SCCB considers these traits and other uniquely human qualities as proxies for the underlying dimension of morality.…”
Section: Concluding Remarks and Future Directionmentioning
confidence: 99%